The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1055/s-0040-1706051
|View full text |Cite
|
Sign up to set email alerts
|

C–H Bond Functionalization of Amines: A Graphical Overview of Diverse Methods

Abstract: This Graphical Review provides a concise overview of the manifold and mechanistically diverse methods that enable the functionalization of sp3 C–H bonds in amines and their derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 466 publications
0
12
0
Order By: Relevance
“…Starting material 2f reacted with bromostyrene 1a , bromomaleate 1d , and bromopyridin-2­(1 H )-one 1g , affording the desired alkenylated products 3p , 3q , and 3r in 62, 65, and 50% yields, respectively. With these challenging substituted and heterocyclic substrates, starting materials 2b – f were easily recycled under the standard conditions. However, the mass balances were high, indicating the high chemoselectivity of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Starting material 2f reacted with bromostyrene 1a , bromomaleate 1d , and bromopyridin-2­(1 H )-one 1g , affording the desired alkenylated products 3p , 3q , and 3r in 62, 65, and 50% yields, respectively. With these challenging substituted and heterocyclic substrates, starting materials 2b – f were easily recycled under the standard conditions. However, the mass balances were high, indicating the high chemoselectivity of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, the crux of the alkylamine dehydrogenation revolves around the cleavage of the unreactive α C−H bond. 6,7 As illustrated in Figure 1b, various strategies have been explored to effect this Cα−H bond cleavage, including deprotonation (H + transfer) with vicinal dicarbonyl reagents, 8 hydrogen atom transfer or single electron transfer/deprotonation, 9−11 and metal-catalyzed hydride (H − ) transfer reactions. 12,13 In addition to metalcatalyzed pathways, hydride transfer within alkylamines can also occur without metal assistance, although primarily in intramolecular settings.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been observed that organic chemists have frequently utilized 1,2,3,4-tetrahydroisoquinolines (THIQs) by activating the α-C­(sp 3 )–H position to produce a large variety of biologically important natural and unnatural compounds . Recently, the functionalization of the C–H bond of amines in general and amines having azomethine ylide intermediates has captured the attention of organic chemists due to the wide applicability of such approaches in the synthesis of desired targets. , It is noteworthy to mention that, in most of the cases, α-C­(sp 3 )–H activation of THIQs has been realized with protected amines …”
mentioning
confidence: 99%